1989
DOI: 10.3109/10715768909087942
|View full text |Cite
|
Sign up to set email alerts
|

Adriamycin Affects Glomerular Renal Function: Evidence for the Involvement of Oxygen Radicals

Abstract: The early nephrotoxic effect of the antitumor drug adriamycin (ADR) is suggested to be related to the generation of oxygen free radicals. Therefore the O2-dependence and the influence of free radical scavengers were studied in the model of the isolated perfused single glomerulus of Myxine glutinosa and by histochemical demonstration of the glomerular ATP-ase. In Myxine, the glomerular ATP-ase activity was decreased after injection of ADR (5 mg/kg, i.v.). Both ADR-treated Myxine and controls were exposed for 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…A common experimental model of proteinuria in rats is ADR induced nephropathy. The mechanism of the glomerular injury in this model is closely related to the generation of reactive oxygen species (ROS) [9,10,11]. ROS-mediated heparan sulfate depolymerization was reported to be associated with the glomerular basement membrane permeability in ADR nephropathy [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A common experimental model of proteinuria in rats is ADR induced nephropathy. The mechanism of the glomerular injury in this model is closely related to the generation of reactive oxygen species (ROS) [9,10,11]. ROS-mediated heparan sulfate depolymerization was reported to be associated with the glomerular basement membrane permeability in ADR nephropathy [10].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of ADR induced nephropathy is related to the generation of reactive oxygen species (ROS). ROS, induced by anthracyline metabolism, damage nucleic acids, inactivate the respiratory chain enzymes and break cellular membranes by increased lipid peroxidation products [9,10,11]. The ensuing histological feature consists of glomerular vacuolization and sclerosis, dilatation of Bowman’s capsule and tubules and interstitial lymphocyte infiltrations [12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ROS were demonstrated to be involved in experimental glomerulopathies such as Adriamycin (ADR) nephropathy (25), puromycin aminonucleoside nephrosis (26), passive Heymann nephritis (27), and anti-GBM nephritis (28). ROS have been shown to cause proteinuria (29,30) and loss of HS in the isolated perfused kidney model (29).…”
Section: Heparan Sulfate (Hs)mentioning
confidence: 99%
“…Identification of the radical(s) primarily involved in HS alteration was performed by the use of specific oxygen radical scavengers. To investigate the physiological significance of ROS on GBM HSPG expression and GBM permeability, we evaluated HS alterations in the nephrotic syndrome in rats after intravenous injection of ADR (doxorubicin, a member of the anthracyclin family), since in this model the generation of ROS has been shown (25,34). The impact of ROS on GBM HSPG and HS expression and albuminuria in this model was investigated by intervention studies with radical scavengers.…”
Section: Heparan Sulfate (Hs)mentioning
confidence: 99%
“…The mechanism(s) by which the aminonucleoside-induced glomerular damage occurs is not clearly understood; however, a role for reactive oxygen species has been implicated as mediators of glomerular injury in several models of kidney disease [3] including aminonucleoside [4] and adriamycin [5] nephrosis. Previous reports have demonstrated that hyperlipidemia has an adverse effect on glomerular function in experimental animals [b, 7].…”
Section: Madrasmentioning
confidence: 99%